The gold-catalyzed hydroarylation of alkynes with electron-rich heteroarenes: a kinetic investigation and new synthetic possibilities - Schießl, Jasmin; Rudolph, Matthias; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2017)
The gold-catalyzed mono-hydroarylation and two-fold hydroarylation of alkynes with electron-rich heteroarenes was analyzed by a 1H NMR kinetic study. The obtained rate constants for the decreasing alkyne concentration provide information on the reactivity of this addition reaction. The examinations show the orthogonal reactivity of gold and a proton for the two reaction steps. The first hydroarylation is exclusively promoted by gold(I), whereas the second step is premised on a proton which will be reversibly derived from the formation of σ,π-acetylide complexes from the terminal alkynes or by interaction with solvents. Based on kinetic data, it was possible to synthesize a large range of mono-adducts in moderate to good yields, furthermore the synthesis of hetero-di-adducts, bearing two different substituents, was explored.